Loss of CD11b Accelerates Lupus Nephritis in Lyn-Deficient Mice Without Disrupting Glomerular Leukocyte Trafficking - Gottschalk, Timothy A.; Hall, Pamela; Tsantikos, Evelyn; L’Estrange-Stranieri, Elan; Hickey, Michael J.; Hibbs, Margaret L. (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a complex, heterogeneous autoimmune disease. A common manifestation, lupus nephritis, arises from immune complex deposition in the kidney microvasculature promoting leukocyte activation and infiltration, which triggers glomerular damage and renal dysfunction. CD11b is a leukocyte integrin mainly expressed on myeloid cells, and aside from its well-ascribed roles in leukocyte trafficking and phagocytosis, it can also suppress cytokine production and autoreactivity. Genome-wide association studies have identified loss-of-function polymorphisms in the CD11b-encoding gene ITGAM that are strongly associated with SLE and lupus nephritis; however, it is not known whether these polymorphisms act alone to induce disease or in concert with other risk alleles. Herein we show using Itgam-/- mice that loss of CD11b led to mild inflammatory traits, which were insufficient to trigger autoimmunity or glomerulonephritis. However, deficiency of CD11b in autoimmune-prone Lyn-deficient mice (Lyn-/-Itgam-/-) accelerated lupus-like disease, driving early-onset immune cell dysregulation, autoantibody production and glomerulonephritis, impacting survival. Migration of leukocytes to the kidney in Lyn-/- mice was unhindered by lack of CD11b. Indeed, kidney inflammatory macrophages were further enriched, neutrophil retention in glomerular capillaries was increased and kidney inflammatory cytokine responses were enhanced in Lyn-/-Itgam-/- mice. These findings indicate that ITGAM is a non-monogenic autoimmune susceptibility gene, with loss of functional CD11b exacerbating disease without impeding glomerular leukocyte trafficking when in conjunction with other pre-disposing genetic mutations. This highlights a primarily protective role for CD11b in restraining inflammation and autoimmune disease and provides a potential therapeutic avenue for lupus treatment.